Differential expression of the MT-1E gene in estrogen-receptor-positive and -negative human breast cancer cell lines - Friedline, JA; Garrett, SH; Somji, S; Todd, JH; Sens, DA (The American journal of pathology, 1998)
The goal of this study was to determine which of the 10 functional metallothionein (MT) genes are expressed in four human breast cancer cell lines and whether expression varies among the cell lines. Using reverse transcription polymerase chain reaction (RT-PCR) technology, it was shown that there was no expression of mRNA for the MT-1A, MT-1B, MT-1F, MT-1G, MT-1H, MT-3, and MT-4 genes in any of the four cell lines. All four cell lines were shown to express mRNA for the MT-2A and MT-1X genes. The expression level of mRNA for the MT-2A gene demonstrated modest differences among the cell lines, whereas expression of the MT-1X gene was consistent. In contrast, mRNA for the MT-1E gene was expressed in only two of the four cell lines and expression correlated to the estrogen receptor status of the cell lines. The two estrogen-receptor-positive cell lines showed no mRNA expression for the MT-1E gene. In the two estrogen-receptor-negative cell lines, mRNA expression for the MT-1E gene was elevated with expression levels similar to the housekeeping gene, glyceraldehyde-3-phosphate dehydrogenase. The cellular content of MT protein was also shown to be elevated in the estrogen-receptor-negative cell lines that express MT-1E mRNA. These results suggest a possible relationship between estrogen receptor status and MT-1E gene expression in human breast cancer.